Identification of high affinity and low molecular alternatives of boceprevir against SARS-CoV-2 main protease: A virtual screening approach - Borkotoky, S.; Banerjee, M.; Modi, G.P.; Dubey, V.K. (Elsevier B.V., 2021)
SARS-CoV-2 has posed global challenge for healthcare due to COVID-19. The main protease (Mpro) of this virus is considered as a major target for drug development efforts. In this work, we have used virtual screening approach with molecular dynamics simulations to identify high affinity and low molecular weight alternatives of boceprevir, a repurposed drug currently being evaluated against Mpro. Out of 180 compounds screened, two boceprevir analogs (PubChem ID: 57841991 and 58606278) were reported as potential alternatives with comparable predicted protease inhibitor potential and pharmacological properties. Further experimental validation of the reported compounds may contribute to the ongoing investigation of boceprevir. © 2021 Elsevier B.V.
Keywords: Virtual screening; SARS CoV-2; Boceprevi; MD simulation; MM-PBSA